A Point Mutation in the Rhesus Rotavirus VP4 Protein Generated through a Rotavirus Reverse Genetics System Attenuates Biliary Atresia in the Murine Model - Mohanty, Sujit K. (J Virol, 2017)
Rotavirus infection is one of the most common causes of diarrheal illness in humans. In neonatal mice, rhesus rotavirus (RRV) can induce biliary atresia (BA), a disease resulting in inflammatory obstruction of the extrahepatic biliary tract and intrahepatic bile ducts. We previously showed that the amino acid arginine (R) within the sequence SRL (amino acids 445 to 447) in the RRV VP4 protein is required for viral binding and entry into biliary epithelial cells. To determine if this single amino acid (R) influences the pathogenicity of the virus, we generated a recombinant virus with a single amino acid mutation at this site through a reverse genetics system. We demonstrated that the RRV mutant (RRV(VP4-R446G)) produced less symptomatology and replicated to lower titers both in vivo and in vitro than those seen with wild-type RRV, with reduced binding in cholangiocytes. Our results demonstrate that a single amino acid change in the RRV VP4 gene influences cholangiocyte tropism and reduces pathogenicity in mice. IMPORTANCE Rotavirus is the leading cause of diarrhea in humans. Rhesus rotavirus (RRV) can also lead to biliary atresia (a neonatal human disease) in mice. We developed a reverse genetics system to create a mutant of RRV (RRV(VP4-R446G)) with a single amino acid change in the VP4 protein compared to that of wild-type RRV. In vitro, the mutant virus had reduced binding and infectivity in cholangiocytes. In vivo, it produced fewer symptoms and lower mortality in neonatal mice, resulting in an attenuated form of biliary atresia.